STUDI KOMPARATIF IMPLEMENTASI HUKUMAN CAMBUK DI ACEH DAN KELANTAN GOOD GOVERNANCE DAN HAK ASASI MANUSIA - Pancasilawati, Abnan (STIT Ibnu Rusyd Tanah Grogot, 2024)
The implementation of caning punishment in Aceh, Indonesia, and Kelantan, Malaysia, reflects differences in applying the principles of good governance and adapting to human rights values. This study aims to analyze the extent to which the implementation of caning punishment in both regions reflects the principles of accountability, transparency, participation, and responsiveness, as well as its contribution to the objectives of Islamic law in maintaining public morality and social order. This research employs a normative-empirical approach with a comparative case study method. Data were obtained through interviews, observations, and legal document analysis. The findings reveal that Aceh excels in transparency and public participation, whereas Kelantan demonstrates stronger administrative accountability and protection of the dignity of offenders. However, there are gaps between the legal norms and their implementation in both regions, influencing public perceptions of justice and the effectiveness of the legal system. The study concludes that the implementation of caning punishment requires policy reforms to integrate the principles of maqasid al-shariah and good governance. This integration aims to establish an effective, inclusive, and responsive Islamic legal system that meets the needs of modern society.